2021
DOI: 10.1111/acer.14702
|View full text |Cite
|
Sign up to set email alerts
|

Patient and provider factors associated with receipt and delivery of brief interventions for unhealthy alcohol use in primary care

Abstract: Background: Unhealthy alcohol use is a serious and costly public health problem. Alcohol screening and brief interventions are effective in reducing unhealthy alcohol consumption. However, rates of receipt and delivery of brief interventions vary significantly across healthcare settings, and relatively little is known about the associated patient and provider factors. Methods: This study examines patient and provider factors associated with the receipt of brief interventions for unhealthy alcohol use in an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 52 publications
2
7
0
3
Order By: Relevance
“…We found that female GPs and those with a longer duration of work experience were more positively impacted by the training intervention. This is consistent with the results of a study from the US that showed that female health care providers and those with longer tenure in the health system were more likely to adopt brief interventions for unhealthy alcohol use in an integrated health care system (30). Another study from the US examining the effectiveness of an SBIRT curriculum for emergency department (ED) staff showed that length of time in practice was positively associated with SBIRT utilization, controlling for gender, race, and type of profession (31).…”
Section: Discussionsupporting
confidence: 90%
“…We found that female GPs and those with a longer duration of work experience were more positively impacted by the training intervention. This is consistent with the results of a study from the US that showed that female health care providers and those with longer tenure in the health system were more likely to adopt brief interventions for unhealthy alcohol use in an integrated health care system (30). Another study from the US examining the effectiveness of an SBIRT curriculum for emergency department (ED) staff showed that length of time in practice was positively associated with SBIRT utilization, controlling for gender, race, and type of profession (31).…”
Section: Discussionsupporting
confidence: 90%
“…For example, the literature suggests that BP check-ups and hypertension awareness were higher among women than men but did not translate into better antihypertensive medication practice,61 and women with T2D exhibit worse control of HbA1c, BP and lipids than men 62–65. Research by our group66 67 and other researchers68 69 also found that women were less likely to receive BI when screened positive for unhealthy alcohol use, but a growing literature has described potential BI adaptations for women70 that might improve outcomes. Future studies, including non-randomised longitudinal studies with appropriate analytical approaches such as MSM-IPW, are also needed to estimate causal effects of BI over time while addressing time-varying confounders, including disease severity, provider attitudes and biases, psychological confounders and corresponding medication adherence.…”
Section: Discussionmentioning
confidence: 71%
“…Excluding patients and providers with missing data, the final analytical sample was 287 551 patients and 2952 providers [52] (Figure 1). This study was approved by the KPNC Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%